A Novel Method to Combine Assessment of Benefit and Harm: Outcome Measures in Rheumatology 3×3 Methodology Applied to Two Active Comparator Trials. Issue 2 (10th January 2019) - Boers, Maarten; Singh, Jasvinder A.; Cofield, Stacey S.; Bridges, S. Louis; Moreland, Larry W.; O'Dell, James R.; Wu, Hongsheng; Leatherman, Sarah; Curtis, Jeffrey R.
Abstract : Objective: The Outcome Measures in Rheumatology (OMERACT) 3×3 method analyzes the occurrence of benefit and harm simultaneously at the individual patient level. We applied this method to 2 recent rheumatoid arthritis (RA) trial data sets. Methods: The Treatment of Early Aggressive Rheumatoid Arthritis (TEAR) and the Rheumatoid Arthritis Comparison of Active Therapies (RACAT) randomized trial outcomes for safety were defined according to OMERACT as having no adverse events (AEs), non‐serious AEs, and serious AEs. Treatment efficacy was defined as good, moderate, or no response. A good treatment response without any AEs was labeled an unqualified success, and no treatment response but at least 1 AE was considered an unmitigated failure. The association between benefit and harm was assessed by chi‐square or exact tests, as appropriate. Results: In TEAR, 612 of 755 patients had response data at 48 weeks: 14% of patients experienced unqualified success and 9% had unmitigated failure, with no difference between the treatment arms. Treatment response and AE rates were not correlated. In RACAT, 309 of 353 patients had response data at 48 weeks: 6% of patients experienced unqualified success and 11% had unmitigated failure, with no differences between the treatment arms. Response and AE rates were negatively correlated. The frequency of AEs and serious AEs increased as response decreased ( P = 0.008). Conclusion: We found some evidence that clinical response may be reduced by the co‐occurrence of AEs.